2014
DOI: 10.1002/gps.4086
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based stress reduction for older adults with worry symptoms and co‐occurring cognitive dysfunction

Abstract: Background Mindfulness-Based Stress Reduction (MBSR) has the potential to reduce worry and improve cognitive functioning. Objectives In this treatment development project, we examined MBSR in older adults with worry symptoms and co-occurring cognitive dysfunction. We examined (1) acceptability of MBSR, (2) whether MBSR needs to be lengthened providing more repetition, (3) MBSR's benefits for worry reduction and cognitive improvements, and (4) continued use of MBSR techniques during follow-up. Method Two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
2
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 63 publications
(73 reference statements)
5
131
2
16
Order By: Relevance
“…Not only previous studies have supported the application of mindfulness-based stress reduction in patients with this disorder (12)(13)(14)(15)(16)(17)(18)(19) but also therapists have supported CBT in patients improvement (20)(21)(22). Furthermore, some studies have investigated MBSR versus CBT (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Not only previous studies have supported the application of mindfulness-based stress reduction in patients with this disorder (12)(13)(14)(15)(16)(17)(18)(19) but also therapists have supported CBT in patients improvement (20)(21)(22). Furthermore, some studies have investigated MBSR versus CBT (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations include failure to not provide details from medical records on veterans' characteristics that could have influenced the effect of treatment, for instance, any significant diagnoses or basic anthropomorphic data; this study is therefore worth following up. 14,15 The studies selected for the review also reported that mindfulness meditation training reduced anxiety symptoms in patients with GAD and improved coping during a laboratory stress paradigm due through greater resilience to stressful psychological questions. 13 MBCT was another method that used mindfulness and aimed to reduce rates of relapse and recurrence of major depression and treatment-resistant depression causing emotional reactivity in mindfulness meditation training.…”
Section: Discussionmentioning
confidence: 99%
“…13 Anxiety disorders are centered on excessive worrying about future events and negative thoughts, and the practice of mindfulness helps individuals focus on the present moment, helping to decrease worry, negative thoughts and feelings, and to ameliorate cognitive dysfunction in older adults. [14][15][16]19 The practice of mindfulness develops a state of acceptance, emphasizing emotional regulation strategies and increasing QoL and thereby decreasing invasive thoughts, anxiety, and depression. 12 Awareness may be one benefit achieved by using stress-reduction techniques in the treatment of mood and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, longitudinal studies which explicitly investigated this question found beneficial effects of meditative practices on age-related cognitive performance (Berk et al 2016;Gard et al 2014;Marciniak et al 2014), cognitive flexibility (Alexander et al 1989;Lenze et al 2014;McHugh et al 2010;Oken et al 2010), task switching capacity (Lavretsky et al 2013;Newberg et al 2010), memory (Sun et al 2013), verbal fluency (Lenze et al 2014), attention (Lavretsky et al 2013;Lenze et al 2014;Newberg et al 2010;Oken et al 2010), and alerting (Oken et al 2010). In addition, meditation was reported to diminish the level of age-related cognitive impairment (Lavretsky et al 2013;Sun et al 2013).…”
Section: Effects Of Meditation On Cognition and Age-related Cognitivementioning
confidence: 99%